Studi Komparatif antara Teori Organisasi Tradisional dan Teori Organisasi Modern dalam Dunia Kerja - Tati Hartati; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the fundamental differences between traditional organizational theory and modern organizational theory, and to convince them of managerial practices in the industrial world. Traditional organizational theories, such as Max Weber's bureaucratic theory and Henri Fayol's classical management principles, emphasize hierarchical structures, formal rules, and operational efficiency. In contrast, modern organizational theories such as open system theory and contingency theory highlight the importance of adaptability, irregularity, and the relationship between the organization and the external environment. This study uses a qualitative descriptive approach with literature study methods and case observations in several industrial companies in Indonesia. The results of the analysis show that traditional theory is still relevant in the context of stable and clearly structured organizations, but modern theory is superior in dealing with the dynamics and current industrial environment. These findings contribute to the understanding of the development of organizational structures that are more contextual and responsive to changing times.